Availability and utilization of sanitation facilities amongst the tea garden population of Jorhat district, Assam - Bora, Parash Jyoti; Das, Bishnu Ram; Das, Netri (International Journal Of Community Medicine And Public Health, 2018)
Background:Globally, 2.3 billion people still do not have basic sanitation facilities such as toilets or latrines. Inadequate sanitation is estimated to cause 280 000 diarrhoeal deaths annually. Tea garden population belonging mostly to lower socio economic class, often lacks access to basic safe drinking water and sanitation. This study aims to assess the availability and utilization of sanitation facilities amongst the tea garden population. Methods:A Community based descriptive cross sectional study was conducted among the people residing in the lines of tea gardens of Jorhat district. Using multistage cluster sampling a total of 540 eligible subjects were selected for our study and they were interviewed using a pre-designed pre-tested schedule. Results:In our study, sanitation facilities were available in 58.9% households of which 83.1% were sanitary type and 69.7% latrines were functional. Out of the 318 respondents who have latrine, 61.1% reported that they use latrine regularly while 64.1% study respondents had the practice of open air defecation. Conclusions:The availability of sanitation facility and latrine utilization rate of the households were not satisfactory. This reflects that various schemes related to sanitation that are planned and implemented by Government have not been reached to the majority of tea tribe population. So an urgent call has to be made to all stakeholders to work in close collaboration to ensure access and utilization of sanitation facilities among the vulnerable tea plantation community.